Commodity production and African migration to Turkey, Now and in the premodern past - (:unkn) unknown (My University, 2024)
African Migration in Turkey is an under-researched area despite the long history of migration between West Africa and the Ottoman Empire and the large number of African migrants in Turkey. The connection of this historical and contemporary migration movement with commodity production reveals not only the basic dynamics and patterns but also the global character of this mobility. While the flow of labor and commodities between Africa and Turkey continues, especially with Turkey's new Africa policy after 2002, African migrants are also implementing their own interests and agendas. Thus, an interdisciplinary approach encompassing history, economics, and anthropology reveals intertwined transformations and networks that provide a perspective for historical changes.
Keywords: African Research